Characterization and Sensitivity Analysis of JIRAM Spectra for Optimizing CH4 and Retrieval - Chiara Castagnoli; Bianca M. Dinelli; Francesca Altieri; Alessandra Migliorini; Alessandro Mura; Roberto Sordini; Federico Tosi; Raffaella Noschese; Davide Grassi; Alberto Adriani; Francesco Biagiotti; Andrea Cicchetti; et al. (The Planetary Science Journal)
Since the Juno spacecraft started orbiting around Jupiter in 2016, our understanding of the planet has continued to expand. One of the mission’s primary scientific objectives was to delve into the mechanisms governing the complex aurorae at Jupiter’s poles, leading to significant progress. The Jovian InfraRed Auroral Mapper (JIRAM), on board the Juno mission and composed of an imager and a spectrometer, strongly contributed to advancing in the field. Throughout the mission, the imager has provided detailed monitoring of auroral morphology in the infrared, while the spectrometer has enabled us to derive the temperature and concentration of H ${}_{3}^{+}$ and the distribution of CH _4 across the planet. Despite the extended data volume provided by the spectrometer, only a small fraction of its observations have been analyzed so far, due to the intricate nature of JIRAM spectra, which pose challenges in modeling the observed signal. As new scientific goals have emerged, further investigation into these data is needed to enhance their characterization. In this study, we present several sensitivity tests on JIRAM spectra, with a specific emphasis on observations taken at nadir. Our aim is to characterize the criticalities of these data and assess the implications for further data analyses using inversion techniques. This research is intended as a valuable reference for future JIRAM spectra exploitation, outlining strategies used to address challenges arising from the nature of the data and identifying areas that still require further investigation.